Ateńskie prawo pogrzebowe - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is devoted to the Athenian funerary law. First, the author presents the duty — which was both religious and legal — to bury the body. Next he provides an in-depth analysis of various funerary laws from Solon to Demetrius of Phaleron as well as the funerary law that Plato provided for his ideal state. The existing laws specified the forms of acceptable human behaviour during funerals, limited their costs, type of sacrifice and size of tombs. Their objective was also to limit the spread in the public sphere of the polis of religious pollution resulting from contact with the deceased. Solon’s funerary law influenced other known Greek regulations dealing with funerals, especially the law of the Labyadai phratry at Delphi, the law of the Ioulis polis on the island of Keos as well as the oldest Roman code of law — the Law of the Twelve Tables.
Keywords: prawo ateńskie; prawo pogrzebowe; Prawo Dwunastu Tablic; Solon; Demetrius z Faleronu; Platon